Does immunotherapy reduce the recurrence rate in nasal polyposis? - T A El-Samny; W F Ezzat; A Ashour Zinab; E K Hakim; M K El Shrnouby; H A El-Melegi; Mohamed Y Attia (SpringerOpen, 2014)
Background Nasal polyposis (NP) is a chronic inflammatory condition with no proved effective long-term treatment and a tendency to recur. Aim The aim of our study was to evaluate the effect of immunotherapy on the recurrence rate of NP in atopic patients after surgical management and the ability to improve the quality of patients' lives and decrease their suffering. Patients and methods We chose 60 patients (discussion with the patients with respect to the benefits and hazards of the study was performed and informed consents were provided) with bilateral NP (as diagnosed by full history taking, clinical examination, nasal endoscopic examination, and sinonasal computed tomography) who proved to be allergic (by full history taking, clinical examination, skin prick test, serum total IgE, serum-specific IgE). We classified them into three groups: group I included 18 patients who underwent surgical management (functional endoscopic sinus surgery) as a control group, group II included 18 patients who underwent treatment with subcutaneous immunotherapy by gradual up-dosing protocol for inhalant allergens as a second control group, and group III included 20 patients who underwent treatment with subcutaneous immunotherapy for inhalant allergens 6 weeks after surgical treatment. Results In the three groups of patients, the sinoNasal Outcom -22 (SNOT-22) scores were significantly decreased (with the minimally important difference greater than 9 points in 17/18 patients in group I, 17/20 patients in group III, and 15/18 patients in group II), denoting significant clinical improvement in the three groups. However, patients treated with surgery and postsurgical immunotherapy reported more improvement, with no significant difference between them, than those treated with immunotherapy alone. Seven (38.9%) patients of group I had recurrence of NP, whereas six (30%) patients of group III had recurrence. On comparison, there was no statistically significant difference between the two groups. In group II, the NP score was declined on immunotherapy alone but did not disappear completely. The timing of recurrence of NP in patients of group I ranged from 7 to 13 months, whereas in group III it ranged from 12 to 16 months. Conclusion We found that immunotherapy could help in improving patients' clinical symptoms and subsequently their quality of life; postoperative immunotherapy in addition can delay the recurrence, although it does not decrease the recurrence rate significantly.